Does Involvement of Military Government Affects FDI Inflow in Pakistan? - Ghullam Mustafa Mir; Muzzamil Hussain (SEISENSE (PRIVATE) LIMITED, 2018)
The purpose of this study is to investigate the role of inflation, exchange rate uncertainty, gross domestic product (GDP) and presence of military government in FDI inflows in Pakistan. Annual data from the 1991-2013 is used to validate the results of the studied variables by using OLS regression. According to the expectations inflation, exchange rate and GDP are significant determinants of the FDI in Pakistan during the period of the study but the presence of military government (MG) has not significant effect on the inflow of the FDI in Pakistan.